Praktik Greenwashing dalam pengungkapan ESG: A Systematic Literature Review - Nurpatwikanto, Widyo; Putra, Ihsan Manshur; Fikrianoor, Kahfi (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research Aim: This study aims to identify current Environmental, Social, and Governance (ESG) practices and evaluate whether company disclosures genuinely reflect sustainability performance or merely highlight favorable aspects. Design/Method/Approach: The research applies a Systematic Literature Review (SLR) approach by reviewing previous studies related to ESG disclosure, corporate performance, and greenwashing behavior from various international journals. Research Finding: The findings reveal that ESG implementation significantly influences a company’s financial performance and the valuation of intangible assets. However, some companies engage in greenwashing to attract investors by overstating their ESG achievements. Theoretical Contribution/Originality: This study contributes to the academic discussion on ESG disclosure by mapping research trends and synthesizing insights from reputable scholars, providing a conceptual understanding of the link between ESG and corporate value. Practitioner/Policy Implication: The results imply that regulators and corporate managers must strengthen transparency and reporting standards to prevent misleading ESG disclosures. Research Limitation: The limitation of this study lies in the restricted number of reviewed articles, which may constrain the comprehensiveness of the analysis.